Analisis Pengaruh Roe, NPM, dan EPS terhadap Harga Saham Perusahaan yang Terdaftar di Bursa Efek Indonesia - Yupianty Yupianty; Anggun Pertama Husda (Program Pascasarjana STIE Amkop Makassar, 2022)
Abstract This study's objective is to examine the impact of stock prices on return on equity (ROE), net profit margin (NPM), and profits per share (EPS) in companies in the food and beverage subsector listed on the Indonesia Stock Exchange for the years 2017 through 2021. The author does quantitative research in her work. The type of information used is secondary information, specifically financial statements downloaded from the website of the Indonesia Stock Exchange. Regression analysis and SPSS assistance are the data analysis techniques employed. According to the findings of the study done using the t test method, return on equity (ROE), net profit margin (NPM), and earnings per share (EPS) had no significant impact on stock prices. The outcomes of the The f test's findings show that earnings per share (EPS), net profit margin (NPM), and return on equity (ROE) all have a significant impact on stock prices at the same time (simultaneously). Keywords:Return On Equity (ROE), Net Profit Margin (NPM), and Earning Per Share (EPS) and Stock Prices